2011
DOI: 10.1590/s0365-05962011000700038
|View full text |Cite
|
Sign up to set email alerts
|

Psoríase eritrodérmica refratária em criança com excelente resposta ao etanercepte

Abstract: Psoriasis affects 0.12% to 0.71% of all chil dren. Erythrodermic pso ria sis is an uncom mon but serious disor der, occur ring in less than 1.5% of cases. Tumor necro sis fac tor-alpha bloc kers (TNF-α) are a new class of drugs used to treat mode ra te to seve re pso ria sis refrac tory to con ven tio nal the ra pies. Etanercept is a TNFα recep tor fusion pro tein, appro ved by the FDA for trea ting juve ni le rheu ma toid arth ri tis. We pre sent the case of a 7-year-old suf fe ring from pla que pso ria sis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…It was then stopped for ineffective results, after a total of ten injections [ 100 ]. Frega et al, however, reported the case of a 7-year-old patient suffering from erythrodermic psoriasis refractory to cyclosporine and methotrexate, responsive to etanercept [ 101 ].…”
Section: Biologic Drugsmentioning
confidence: 99%
“…It was then stopped for ineffective results, after a total of ten injections [ 100 ]. Frega et al, however, reported the case of a 7-year-old patient suffering from erythrodermic psoriasis refractory to cyclosporine and methotrexate, responsive to etanercept [ 101 ].…”
Section: Biologic Drugsmentioning
confidence: 99%
“…Tumor Necrosis Factor (TNF) Antagonist Etanercept Etanercept, a recombinant human fusion protein, has demonstrated efficacy in treating EP. [49][50][51][52][53][54] Esposito et al reported that with 25 mg twice weekly, a treatment response could be observed between week 12-24. 49 At week 12, five of ten (50%) patients achieved PASI 75, and at week 24, six of ten (60%) patients achieved or maintained PASI 75, and two of ten patients (20%) maintained improvement between PASI 50 and PASI 75.…”
Section: Mycophenolate Mofetil (Mmf)mentioning
confidence: 99%
“…One of these patients was even continued on maintenance therapy for 2 years with lasting remission. 10 , 19 , 64 …”
Section: Systemic Agentsmentioning
confidence: 99%
“… 43 , 68 Methotrexate has been combined with several other agents for the treatment of EP, including with infliximab 55 , 69 71 ; with etretinate reporting satisfactory results 72 ; and with cyclosporine or etanercept reporting excellent results. 64 , 73 …”
Section: Systemic Agentsmentioning
confidence: 99%
See 1 more Smart Citation